Analysis of the environmental impacts caused by the implementation of wind farms in the Seridó Paraibano (Research, Society and Development, 2022)
Wind energy is an alternative source of electricity production that has been developing considerably in Brazil, mainly in the Northeast and in the State of Paraíba. Given this scenario, this study aimed to analyze the implementation of wind farms in the sertão of Paraíba. To achieve this objective, a study was carried out on the socio-environmental conflicts caused by the installation of wind farms, discussing the procedure adopted for the licensing of undertakings of this nature. In conclusion, it was noticed that the environmental discourse of clean energy has concealed rampant deforestation practices, impact on the soil, compromising water resources and the local fauna and flora, increased noise and pollution of the landscape, elements that could be managed throughout the process as a whole, if there were serious inspection in these places and greater action by the public sector responsible for these types of undertakings.